Kajian Linguistik Kognitif Pada Imbuhan Ber- dalam Bahasa Indonesia - Riki Nasrullah; Arip Budiman (Badan Pengembangan dan Pembinaan Bahasa, 2022)
Academic discourse on beR- affixes in Indonesian has been widely studied and analyzed. Generally, the studies only focus on three main valences: form, structure, and meaning. In its development, cognitive linguistics can be another alternative to examine beR- affixes in Indonesian by looking at the symptoms of expanding their meaning. By basing on the theory of categorization of prototype meanings and expansion meanings, cognitive linguistics is felt to be able to answer problems that often arise in the realm of beR- meaning meanings that tend to overlap. The results of this study suggest that cognitive linguistics can be an alternative study to fill the gaps in the study of beR- affixes in Indonesian. From the perspective of cognitive linguistics, the meanings present in the beR affix can be said to have expansion symptoms. The categorization analysis can see this of the meaning of the prototype and the meaning of its expansion. The prototype meaning of ¬beR- is mainly